Alantolactone and ZnO nanoparticles induce apoptosis activity of cisplatin in an ovarian cancer cell line (SKOV3) - Shahriar Alipour; Ghader Babaei; Shiva Gholizadeh-Ghaleh Aziz; Somayeh Abolhasani (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Ovarian cancer is one of the leading causes of cancer mortality in women. Despite the increase in cases of this cancer, the current therapeutic strategy is not effective. This study aimed to investigate the effect of cisplatin (Cis) with alantolactone (ALT) and ZnO nanoparticles (ZnONPs) in inducing apoptosis in SKOV3 ovarian cancer cells line. Experimental approach: To evaluate the viability of SKOV3 cells and determine the IC50 of Cis, ALT, and ZnONPs, MTT assay was used. Real-time PCR and western blotting were used to evaluate the expression levels of genes (XIAP, cyclin D1, Bcl-2, Bax, and MDM2) and proteins (XIAP, cyclin D1, Bcl-2, Bax), respectively. Also, cellular ROS levels were assessed by fluorimetry. Findings / Results: Our results showed that ALT and ZnONPs significantly increased the response to Cis in SKOV3 cells compared to the control and this response is remarkably increased in the triple combination (ALT-Cis-ZnONPs). The expression of XIAP, cyclin D1, and Bcl-2 genes and proteins in the groups treated with ALT, Cis, and ZnONPs as a single agent, double and triple combination were significantly reduced compared to the control, while Bax was generally shown an increase. Also, the level of intracellular ROS is higher in the treatment groups than in the control group and the highest increase was observed in the triple combination. Conclusion and implications: Taken together, our data demonstrated the potential therapeutic approach of using ALT and ZnONPs that may enhance the apoptotic effects of Cis on the SKOV3 cells.